Analysis of Financial Management in Micro and Small Enterprises in Gresik Regency - Wasti Reviandani (Danadyaksa: Post Modern Economy Journal, 2026)
This study discusses the analysis of financial management in micro and small enterprises in Gresik Regency. The purpose of this study is to determine and analyze financial management in Micro and Small Enterprises (MSMEs) in Gresik Regency, identify the obstacles faced, and provide strategic recommendations to improve the effectiveness of financial management. The research method uses a descriptive qualitative method. Data analysis techniques used include data reduction, data presentation, and drawing conclusions to produce systematic interpretations. The results of this study indicate that the financial management of MSMEs in Gresik Regency is still simple and does not comply with good accounting standards. The main obstacles include low financial understanding, a lack of systematic record keeping, and the lack of separation between personal and business finances. Therefore, increasing financial literacy, human resource competency, and the use of financial technology are important strategies in improving the quality of financial management.